Rancang Bangun Sistem Konveyor Berbasis Internet Of Thing (IOT) - Tugino (ReTII, 2019)
The development of electronic technology, especially in the industrial world plays an important role in the production process. Currently there are many machines that calculate the number of manufactured goods. But the counting machine is only able to count the number of items without storing the large number of items that have been produced and there are still those that are not equipped with a monitoring system. Workers must make a report for the amount of goods that have been produced. This can affect the production process which will grow longer and is also very dependent on the limitations of human labor. Conveyor system design uses Raspberry pi model B and Arduino as a control system and HMI. The Optocoupler sensor is used to calculate the number of rotations when the conveyor drive dc motor has started operating. The data obtained will then be displayed on the LCD touchscreen by Raspberry Pi and will also be sent to the server so that it can be monitored online. Besides being displayed, the user can control the speed of the conveyor and also provide setpoints for goods count. The results of this study are the Conveyor System which can be monitored online or offline. Motor speed regulation can also be done by giving pwm to enable motor driver pin. The reading of the motor RPM by using the optocoupler also has very little error, at 4.1%.